Analisis Struktur Film Tipis Disperse Orange-3 Hasil FTIR - Olivia Kombongkila; Heindrich Taunaumang; Farly Reynol Tumimomor (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2024)
A thin film is a material that coats a substrate with a thickness of not more than 10 µm. Thin film technology has undergone many developments, both in terms of the method of manufacture, the materials used and their application in technology. The linear formula of the DO3 molecule is as follows: = and molecular weight of this is 242.23. The purpose of this study was to determine the molecular structure of the FTIR-resulted DO3 thin films. The result of this research was wave number 3434 cm-1 has O-H molecular structure, 3404 cm-1 has O-H molecular structure, 3128 cm-1 has N-H molecular structure, 2927 cm-1 has C-H molecular structure, 1641 cm-1 has C=C molecular structure, 1600 cm-1 has C=C molecular structure, 1513 cm-1 has C=C molecular structure molecule 〖NO〗_2, 1456 cm-1 has a molecular structure C-H, 1425 cm-1 has a molecular structure C-H, 1393 cm-1 has a molecular structure N=N, 1342 cm-1 has a molecular structure 〖NO〗_2 , 1139 cm-1 has a molecular structure C-N, 1133 cm-1 has a molecular structure C-N molecule, 1107 cm-1 has a C-N molecular structure, 1043 cm-1 has a C-O molecular structure, 856 cm-1 has a C-H molecular structure, 831 cm-1 has a C-H molecular structure, 754 cm-1 has a C-H molecular structure, and 658 cm-1 has a C-C molecular structure.